Effect Of Acetosyringone And Callus Age On Transformation For Scutellum - Derived Callus Of Rice - R. M. TRIPATHI,; H. S. BISHT,; R.P. SINGH, (International Journal of Pharma and Bio Sciences, 2010)
An efficient and reproducible protocol for Agrobacterium- mediated transformation of an agronomically useful Oryza sativa variety, Pusa Basmati- 1 (IET- 10364) has been standardized. Although several reporters have been claimed the Agrobacterium- mediated transformation but here we studied the effect of acetosyringone and age of callus on transformation frequency for scutellum- derived callus of Pusa basmati- 1. By optimizing these two parameters for Agrobaterium- mediated transformation, we can produce an efficient and reproducible protocol. The callus derived from mature rice seeds were used as explants for transformation studies. Callus were co-cultured with Agrobacterium tumefaciens EHA 105 harboring a binary vector p35SGUSINT that carried Beta- glucuronidase (uid A) and It contains gene npt II, determining resistance to kanamycin, under the control of the constitutive (nos) promoter. Maximum Agrobacterium- mediated transformation frequency was observed at 350mM/l acetosyringone with 35 days old callus.